(untitled) (Law, State and Telecommunications Review, 2012)
This paper determines the relationship between “freedom of speech”, “freedom of press” and “right to communicate” in the international context of NWICO by way of analyzing the legal reform of 2009 on the Argentinean communications law. The study goes deep in the review of the literature applied to the Argentinean case, in order to specify the origin of the aforementioned terms and conceptual changes experienced since the liberal revolutions to date. It concludes that there is no opposition between freedom of speech and right to communicate or between freedom of speech and regulation, as one can see in the Argentinean case, which adopted a redefinition of the meaning of freedom of speech since the approval of the new broadcasting act.